Empowerment Cadres of Muslimat Nahdlatul Ulama in Stunting Prevention through Nutrition Education in Bangil Pasuruan - Wiwik Winarningsih; Warda El Maida Rusdi; Muhammad Fifin Kombih; Aufar Zimamuz Zaman Al Hajiri; Rima Isna Rahmawati (UNUSA Press, 2023)
Stunting is one of the nutritional problems faced in the world. The prevalence of stunting in Indonesia is 24.4%, while in Pasuruan Regency it is 22.5%. Most people may not understand the term stunting. The purpose of this community service activity is to increase the knowledge of Muslimat Nahdlatul Ulama (NU) cadres in preventing stunting through nutrition education at Bangil Pasuruan. Method: The target participants for this activity are the Management of the NU Bangil Pasuruan Muslimat Branch. The pre-test and post-test were given as a measure of the participant's level of knowledge after being given education. The provision of this education uses electronic media, namely Power Point regarding inviting toddlers and toddler mothers to come regularly to attend